PEMBERDAYAAN EKONOMI MASYARAKAT DI DESA PEMATANG BERANGAN KECAMATAN RAMBAH KABUPATEN ROKAN HULU - ", Fahrijul; ", Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research is an analysis of how Pematang Jaya BUMDes in Pematang Berangan Village develope the economy of the community in improving the economic welfare of the community. The purpose of this study is to find out how BUMDes empower the economy of the community in improving the welfare of the people of Pematang Berangan Village through a savings and loan program. Then how to use the loan funds by the community, as well as the factors that influence the return of loan funds from BUMDes Pematang Jaya. This research was conducted in Pematang Berangan Village, Rokan Hulu Regency, Riau Province.This research use desciptive quantitative approach. Data collection is done through interviews, observation and documentation. Sampling was done by purposive sampling, namely the sample used was residents who used loan funds with a total of 10% of 834 people, as many as 83 people. The results of this study, namely BUMDes Pematang Jaya, have greatly helped the community in the economic movement in Pematang Berangan Village. However, the use of community loan funds has not been maximized in using the funds so that it is not in accordance with the wishes of BUMDes and has resulted in the return of the loan being choked up.    Keyword: BUMDes, Community Economy, Pematang Berangan Village.